The "Indians of Palmares": Conquest, Insurrection, and Land in Northeast Brazil. - Hertzman, Marc A. (Hispanic American Historical Review, 2023)
This article examines a group that has received little scholarly attention: the Indigenous people of Palmares, the site of one of history's largest fugitive slave communities, defeated by the Portuguese in 1695. What studies do exist emphasize origins: Did Indigenous people help build the fugitive settlements of Palmares? I instead focus on the post-1695 period, when competing actors sought land in the interior regions that the settlements once occupied. Shaped by displacement and diaspora, during the eighteenth and nineteenth centuries some Indigenous people rebelled, while others referenced their role as conquerors of Palmares to make land claims. Though discursive representations of Indigenous roles as conquerors rarely prevented material dispossession, the communities persisted despite remarkable challenges. Their trajectories indicate new ways to think about Palmares and Indigenous history and provide suggestive points of comparison with Spanish America and better-known examples from the Age of Revolution.